“If I Should Die”: Attitudes to the Dead Hero in British Poetry of the Great War - D. Rácz, István (Hungarian Journal of English and American Studies, 2021)
When we read the poems of the Great War today, we interpret them both as historical documents and as works of art. World War I poetry wished to open the readers’ eyes to the horror that they were unable to imagine in the home country. As a consequence, the representation of the victim position proved to be particularly important both in populist texts (such as John McCrae’s “In Flanders Fields”) and in poems undermining the conventional idea of heroism (such as those by Charles Sorley, Wilfred Owen, Edmund Blunden). Furthermore, a comparison between two poems about war heroes, Rupert Brooke’s “The Soldier” and Yeats’s “An Irish Airman Foresees His Death” demonstrates the difference between war poetry and modernist literature. Yeats views and considers the problem of the dead hero from a distance, whereas Brooke represents his own situation from within. Both texts (although very different both in character and in artistic value) contribute to our better understanding of the war experience. (IDR)